المفهوم القانوني لمهمة مراقب الحسابات في الشركة الخاضعة لرقابته وفقاً للأنظمة السعودية - أحمد عبد الرحمن المجالي, أحمد (revue mofakir, 2018)
The importance of research, in the legal concept of the role of the auditor in the company that under is his control, appear in defining the relationship between the auditor and the company under his control, to determine this relationship, three theories have emerged, namely: Traditional theory: this theory emphasizes the contractual nature of this relationship, it decide that the auditor is like an agent for all shareholders in the company. Legal theory: this theory contends that the company is a full legal personality subject to the provisions of the Companies Act. Finally mixed theory: this theory considers that the company is a contract organized by the parties in accordance with the provisions of the law. The importance of this research is, also, reflected in the determination of the real role of the auditor in the company that is under his control, sometimes because of the magnitude of some companies, only one auditor cannot accomplish his task, so it might do the audit more than one, for that, this research will help determine who is the real auditor, once determine the real auditor, we can identify the person responsible for detecting errors and illegal acts in the company's accounts, For that Saudi legislator organized auditor’s profession in Saudi Companies Law issued by Royal Decree No. (6) for the year 1385 AH, dedicated to this profession a full chapter in (articles 129-133),also, Saudi Chartered Accountants ActIssued in 1412 AH, Explain the functions of the auditor, highlighted his rights and his duties.